2013
DOI: 10.1161/circulationaha.113.002472
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Diabetes Mellitus on Inappropriate and Appropriate Implantable Cardioverter-Defibrillator Therapy and Mortality in the Multicenter Automatic Defibrillator Implantation Trial–Reduce Inappropriate Therapy (MADIT-RIT) Trial

Abstract: T he Multicenter Automatic Defibrillator Implantation TrialReduce Inappropriate Therapy (MADIT-RIT) showed that innovative implantable cardioverter-defibrillator (ICD) programming was associated with a reduction in inappropriate therapy and mortality.1 The MADIT-RIT trial randomized patients with a primary prophylactic ICD indication to 3 different types of ICD programming: conventional programming with a ventricular tachycardia (VT) zone of 170 to 199 bpm, high-rate cutoff with a VT zone ≥200 bpm, or 60-secon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 41 publications
1
23
0
Order By: Relevance
“…Both arms (ii) and (iii) were associated with a significant reduction in appropriate and inappropriate ICD therapy [29•]. In addition to more ICD shocks, there was a significant three-five fold greater use of ATP in the conventional programming control arm versus the comparator arms.…”
Section: Limitations Of the S-icd: Bradycardia Pacing And Anti-tachycmentioning
confidence: 99%
“…Both arms (ii) and (iii) were associated with a significant reduction in appropriate and inappropriate ICD therapy [29•]. In addition to more ICD shocks, there was a significant three-five fold greater use of ATP in the conventional programming control arm versus the comparator arms.…”
Section: Limitations Of the S-icd: Bradycardia Pacing And Anti-tachycmentioning
confidence: 99%
“…For example, in a study of 194 006 patients with an ICD, Saxon and colleagues reported an ICD discharge rate of ≈18% over a similar follow‐up period 44. The mechanisms for the small differences in ICD discharge rate in our presumed uninfected population are unclear but are likely, in part, mediated by a high background prevalence of diabetes mellitus,46 cocaine use,26 and the lower rate of cardiac resynchronization therapy use 47. Finally, the interpretation of the ICD data was derived from the EHR from the interpretation of a board‐certified electrophysiologist and was not independently reviewed.…”
Section: Discussionmentioning
confidence: 88%
“…This is in concordance with the post hoc sub group analyses of the comparison of medical therapy, pacing, and defibrillation in heart failure (COMPANION) and multicenter automatic defibrillator implantation trial (MADIT)II trials that did not find an increased rate of appropriate therapies in the DM cohort [28,29]. However, a recent sub-study of the multicenter automatic defibrillator implantation trial-reduce inappropriate therapy (MADIT RIT) did find that DM patients had a 58% increased risk of appropriate therapy (p = 0.003), but a 46% decreased risk of inappropriate therapy (p = 0.002) compared to no DM patients during a mean follow up of 17 months [14]. The authors suggested that the increased risk for appropriate ICD therapy might be explained by a reduced autonomic function or vulnerable myocardium resulting from ischemia and fibrosis in DM patients rendering the myocardium more prone to produce ventricular arrhythmias.…”
Section: Discussionmentioning
confidence: 98%
“…DM is a risk factor for development of atrial fibrillation [7,13,[36][37][38] and indeed, more of our patients had atrial fibrillation (Table 1), a major cause of inappropriate shocks, and it would be anticipated that the rate of inappropriate shocks would be increased. Evidence based programming of these devices has greatly decreased the rate of inappropriate therapies especially in diabetics [14] and indeed several centers contributing to the registry were participants in successful programming trials during the course of follow up, which may explain why there was no difference in the rate of inappropriate therapies [14,39].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation